Comparative analysis of psychological characteristics of representatives of different adolescent subcultures - Rezida R. Khusnutdinova; Nailya G. Khakimova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper discusses the psychological characteristics of adolescence. In order to manage the process of socialization of adolescents and build a prevention line, knowledge of the school environment is necessary. The most common subcultures in the adolescent environment are highlighted. A comparative analysis of the psychological characteristics of adolescents belonging to different subcultures is carried out. Differences in self-assessment of interpersonal relationships, motivation for affiliation, aggressiveness and socio-psychological adaptation among adolescents were revealed.